The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5539/jfr.v3n5p8
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameters and Bioactive Compounds of Red Tomatoes (Solanum lycopersicum L.) cv Roma VF at Different Postharvest Conditions

Abstract: Tomato is one of the most important crops at worldwide; however, much of the production is lost during the postharvest due to the inadequate storage conditions. The aim of this study was to evaluate the effects of different postharvest conditions on some quality and bioactive parameters of tomatoes. Tomatoes Roma VF variety were stored at three temperature (7, 22, and 37 °C) to evaluate some physicochemical characteristics (pH, total soluble solids, titratable acidity, color, and firmness) and bioactive compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…Batu (2004) reported that a firmness greater than 8.76 N was very firm and very marketable in supermarkets, hence, the result of this experiment is in agreement with the author's report. Moreover, the tomatoes stored inside an EC environment had higher firmness, compared to those stored under ambient conditions, which is in agreement with the report of Luna-Guevara et al (2014). The result indicates that EC storage kept the fruit structure intact and firm, which might contribute to the maintenance of tomato quality.…”
Section: Firmnesssupporting
confidence: 90%
“…Batu (2004) reported that a firmness greater than 8.76 N was very firm and very marketable in supermarkets, hence, the result of this experiment is in agreement with the author's report. Moreover, the tomatoes stored inside an EC environment had higher firmness, compared to those stored under ambient conditions, which is in agreement with the report of Luna-Guevara et al (2014). The result indicates that EC storage kept the fruit structure intact and firm, which might contribute to the maintenance of tomato quality.…”
Section: Firmnesssupporting
confidence: 90%
“…The difference in the values is due to both the harvesting phase and to the hybrids studied, singularising the Sacher F 1 , Tiger F 1 and Cemil F 1 with higher values. The recorded values are comparable to those obtained by Duma et al (2015); Luna-GuevarA et al (2014) and Oliveira et al (2013). The results of the analyses which refer to the tomato fruit acidity are presented in Table 3.…”
Section: Resultssupporting
confidence: 82%
“…Antioxidant capacity was determined according to Luna-Guevara et al (2014). One milliliter of extract was mixed with 1 mL of DPPH radical at 0.004%, and stored for 30 min in dark environment at room temperature.…”
Section: Antioxidant Capacity (Dpph Method)mentioning
confidence: 99%